Efficacy and safety of helical tomotherapy with daily image guidance in anal canal cancer patients. (2nd June 2016) - De Bari, Berardino; Jumeau, Raphael; Bouchaab, Hasna; Vallet, Véronique; Matzinger, Oscar; Troussier, Idriss; Mirimanoff, René-Olivier; Wagner, Anna Dorothea; Hanhloser, Dieter; Bourhis, Jean; Ozsahin, Esat Mahmut
Abstract: Background and purpose Intensity-modulated radiotherapy (IMRT), also using volumetric modulated arc therapy (VMAT) and helical tomotherapy (HT) techniques, has been only recently introduced for treating anal cancer patients. We report efficacy and safety HT, and daily image-guided RT (IGRT) for anal cancer. Materials and methods We retrospectively analyzed efficacy and toxicity of HT with or without chemotherapy for anal cancer patients. Local control (LC) and grade 3 or more toxicity rate (CTC-AE v.4.0) were the primary endpoints. Overall (OS), disease-free (DFS), and colostomy-free survival (CFS) are also reported. Results Between October 2007 and May 2014, 78 patients were treated. Fifty patients presented a stage II or stage IIIA (UICC 2002), and 33 presented a N1–3 disease. Radiotherapy consisted of 36 Gy (1.8 Gy/fraction) delivered on the pelvis and on the anal canal, with a sequential boost up to 59.4 Gy (1.8 Gy/fraction) delivered to the anal and to nodal gross tumor volumes. Concomitant chemotherapy was delivered in 73 patients, mainly using mitomycin C and 5-fluorouracil ( n  = 30) or mitomycin C and capecitabine combination ( n  = 37). After a median follow-up period of 47 months (range 3–75), the five-year LC rate was 83.8% (95% CI 76.2–91.4%). Seven patients underwent a colostomy because of local recurrence ( n  = 5) or pretreatment dysfunction ( n  = 2). Overall incidence of grade 3 acute toxicity was 24%, mainly as erythema ( n  = 15/19) or diarrhea ( n  = 7/19). Two patients presented a late grade 3 gastrointestinal toxicity (anal incontinence). No grade 4 acute or late toxicity was recorded. Conclusions HT with daily IGRT is efficacious and safe in the treatment of anal canal cancer patients, and is considered in our department standard of care in this clinical setting.